Regulation of ethanol intake under chronic mild stress: roles of dopamine receptors and transporters - Delis, Foteini; Rombola, Christina; Bellezza, Robert; Rosko, Lauren; Grandy, David K.; Volkow, Nora D.; Thanos, Panayotis K. (Frontiers in Behavioral Neuroscience, 2015)
Studies have shown that exposure to chronic mild stress decreases ethanol intake and preference in dopamine D2 receptor wild type mice (Drd2 +/+), while it increases intake in heterozygous (Drd2 +/-) and knockout (Drd2 -/-) mice. Dopaminergic neurotransmission in the basal forebrain plays a major role in the reinforcing actions of ethanol as well as in brain responses to stress. In order to identify neurochemical changes associated with the regulation of ethanol intake, we used in vitro receptor autoradiography to measure the levels and distribution of dopamine D1 and D2 receptors and dopamine transporters (DAT). Receptor levels were measured in the basal forebrain of Drd2 +/+, Drd2 +/-, and Drd2 -/- mice belonging to one of four groups: control (C), ethanol intake (E), chronic mild stress exposure (S), and ethanol intake under chronic mild stress (ES). D2 receptor levels were higher in the lateral and medial striatum of Drd2+/+ ES mice, compared with Drd2+/+ E mice. Ethanol intake in Drd2+/+ mice was negatively correlated with striatal D2 receptor levels. D2 receptor levels in Drd2 +/- mice were the same among the 4 treatment groups. DAT levels were lower in Drd2 +/- C and Drd2 -/- C mice, compared with Drd2 +/+ C mice. Among Drd2 +/- mice, S and ES groups had higher DAT levels compared with C and E groups in all regions examined. In Drd2-/- mice, ethanol intake was positively correlated with DAT levels in all regions studied. D1 receptor levels were lower in Drd2 +/- and Drd2 -/- mice, compared with Drd2 +/+, in all regions examined and remained unaffected by all treatments. The results suggest that in normal mice, ethanol intake is associated with D2 receptor-mediated neurotransmission, which exerts a protective effect against ethanol overconsumption under stress. In mice with low Drd2 expression, where DRD2 levels are not further modulated, ethanol intake is associated with DAT function which is upregulated under stress leading to ethanol overconsumption.